2012
DOI: 10.4039/tce.2012.71
|View full text |Cite
|
Sign up to set email alerts
|

Douglas-fir cone gall midges respond to shape and infrared wavelength attributes of host tree branches

Abstract: We tested the hypothesis that the conophagous Douglas-fir cone gall midge, Contarinia oregonensis Foote (Diptera: Cecidomyiidae), responds to infrared (IR) radiation and other electromagnetic wavelengths associated with cones of Douglas-fir, Pseudotsuga menziesii (Mirbel) Franco (Pinaceae). Early-season (March–April) thermographic images showed that cone orientation (upright, horizontal, pendant) and cone colour (green, purple, green/purple) did not affect apparent cone temperature (inferred from thermographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…anemophilous, the color of cones would not need to attract pollinators. In female cones, this has been discussed in the context of three hypotheses: thermoregulation, photoprotection, and anti-herbivory [21][22][23]34]. However, there are no studies that focused on male cone color and its adaptive implications.…”
Section: Plos Onementioning
confidence: 99%
“…anemophilous, the color of cones would not need to attract pollinators. In female cones, this has been discussed in the context of three hypotheses: thermoregulation, photoprotection, and anti-herbivory [21][22][23]34]. However, there are no studies that focused on male cone color and its adaptive implications.…”
Section: Plos Onementioning
confidence: 99%
“…However, pheromone-baited traps are indirect estimators of female abundance. Zahradnik et al (2012) found that adult midges were attracted to specific infrared radiation and traps constructed to emit this radiation attract both males and females, providing a better estimate of midge numbers.…”
Section: Continuous Improvement Of Methodsmentioning
confidence: 99%
“…Visual cues: These are used when there is a difference between cone and foliage colour. Colour cues are important in some species (e.foliage is used by L. occidentalis in finding its host(Takacs et al 2008), though this was later challenged by Schneider (2014).• Shape and size of reproductive structures: Though this has been implicated in host defense and utilization, little has been found regarding host orientation Zahradnik et al (2012). found that branch-shaped (long and thin) but not barrel-shaped (short and wide) silhouettes are attractive to C. oregonensis, possibly indicating that branches are used in orientation towards the cone-bearing portions of Douglas-fir.…”
mentioning
confidence: 99%